Linking Climate Change and Sustainable Development Goals: Evidence from Pakistan - Munir Ahmad; Prof. Dr. Muhammad Munir (Dialogue Social Science Review (DSSR), 2025)
Climate change remains a potent threat to the worldwide quest for the Sustainable Development Goals (SDGs), and developing nations are particularly vulnerable. This study examines the impacts of climate-induced hazards on SDG 1 No Poverty, 2 Zero Hunger, 3 Good Health and Well-being, 6 Clean Water and Sanitation, 13 Climate Action, and 15 Life on Land in Pakistan. Adopting a mixed-methods research approach, the study incorporated a quantitative survey of 200 stakeholders in Punjab and Sindh with qualitative findings from semi-structured interviews and analysis of policy documents. The results show that a high propensity to recurrent floods, extended droughts and heatwaves severely impact agricultural output, increase the rate of poverty, worsen food shortages, overburden public health systems and expedite ecosystem loss. Political discrimination and inadequate finances have been identified as obstacles to the implementation of SDG indicators, while statistical correlates have indicated strong relationships with climate risks. The study made a case also for the integration of climate action, i.e. mainstreaming into SDGs strategies through among others; climate-smart agriculture, water conservation, community-based adaptation and climate financing if development must be resilient to climate change. This evidence is valuable for global debates to align the climate and development agendas, as well as designing policy pathways that can inform Pakistan's advance towards Agenda 2030. Keywords; Climate Change; Sustainable Development Goals (SDGs); Poverty; Food Security; Public Health; Green Theory